Cognitive Aids With Roles Defined (CARD) for Obstetrical Crises: A Multisite Before-and-after Cohort Study. Issue 2 (June 2021) - Boet, S.; Posner, G.; Bariciak, E.; Crooks, S.; Mitchell, A.; Bryson, G.L.; Burns, J.K.; Bould, M.D.
Abstract : ( Can J Anesth/J Can Anesth . 2020;67:970–980) During critical events, an interprofessional team's coordinated response directly affects patient outcomes. Improvement for such responses may occur through the use of cognitive aids, which can lessen the dependence on memory for healthcare providers in critical situations. A new type of cognitive aid, cognitive aids with roles defined (CARD), allows for clarification of crisis roles using a system of cards assigned to particular team members in order to remind the wearers of their assigned tasks. In the event of a crisis, those without cards are asked to remain in the room away from the patient while waiting for instructions from a Code Leader. The purpose of this study was an evaluation of the CARD system for emergency cesarean deliveries. The primary hypothesis of the study was the CARD system would reduce delivery time. In addition, they hypothesized the CARD system would improve overall clinical outcomes for mother and baby (as compared to traditional emergency cesarean management without CARD).